A species-specific cluster of defensin-like genes encodes diffusible pollen tube attractants in Arabidopsis. - Hidenori Takeuchi; Tetsuya Higashiyama (PLoS Biology)
Genes directly involved in male/female and host/parasite interactions are believed to be under positive selection. The flowering plant Arabidopsis thaliana has more than 300 defensin-like (DEFL) genes, which are likely to be involved in both natural immunity and cell-to-cell communication including pollen-pistil interactions. However, little is known of the relationship between the molecular evolution of DEFL genes and their functions. Here, we identified a recently evolved cluster of DEFL genes in A. thaliana and demonstrated that these DEFL (cysteine-rich peptide [CRP810_1]) peptides, named AtLURE1 peptides, are pollen tube attractants guiding pollen tubes to the ovular micropyle. The AtLURE1 genes formed the sole species-specific cluster among DEFL genes compared to its close relative, A. lyrata. No evidence for positive selection was detected in AtLURE1 genes and their orthologs, implying neutral evolution of AtLURE1 genes. AtLURE1 peptides were specifically expressed in egg-accompanying synergid cells and secreted toward the funicular surface through the micropyle. Genetic analyses showed that gametophytic mutants defective in micropylar guidance (myb98, magatama3, and central cell guidance) do not express AtLURE1 peptides. Downregulation of the expression of these peptides impaired precise pollen tube attraction to the micropylar opening of some populations of ovules. Recombinant AtLURE1 peptides attracted A. thaliana pollen tubes at a higher frequency compared to A. lyrata pollen tubes, suggesting that these peptides are species-preferential attractants in micropylar guidance. In support of this idea, the heterologous expression of a single AtLURE1 peptide in the synergid cell of Torenia fournieri was sufficient to guide A. thaliana pollen tubes to the T. fournieri embryo sac and to permit entry into it. Our results suggest the unique evolution of AtLURE1 genes, which are directly involved in male-female interaction among the DEFL multigene family, and furthermore suggest that these peptides are sufficient to overcome interspecific barriers in gametophytic attraction and penetration.